EFFECT OF WORK FROM HOME ON EMPLOYEE PERFORMANCE THROUGH MOTIVATION, JOB SATISFACTION, AND WORK ENVIRONMENT AS INTERVENING VARIABLES AT PT CITRA TUBINDO TBK - Engelin Manopo, Maya; Khaddafi, Muammar; Catra Yasa, I Wayan; Satriawan , Bambang; Fatahurrazak, Fatahurrazak (CV. Radja Publika, 2022)
The purpose of this study was to determine and analyze the effect of work from home on employee performance through motivation, job satisfaction, and work environment as intervening variables. The method used in this study is a quantitative method. Collecting data using questionnaires and distributed to 111 respondents. Statistical data analysis using SEM-PLS (Structural Equation Modeling-Partial Least Square) and using path analysis to test the pattern of relationships that reveal the influence of variables on other variables, both direct and indirect effects assisted by SmartPLS ver.3.0 software. The results in this study indicate that Work From Home has a positive and significant effect on employee performance with a P-value of 0.000 <0.05. Work From Home has a positive and significant effect on Motivation P-value of 0.000 <0.05. Work From Home has a positive and significant effect on Job Satisfaction P-value of 0.000 <0.05. Work From Home has a positive and insignificant effect on the work environment. P-value is 0.679>0.05. Motivation has a positive and significant effect on Employee Performance P-value of 0.000 <0.05. Job Satisfaction has a positive and significant effect on Employee Performance P-value of 0.003 <0.05. Work Environment has a positive and significant effect on Employee Performance P-value of 0.000 <0.05. Work From Home has a positive and significant effect on Employee Performance through Motivation P-value of 0.007 <0.05. Work From Home has a positive and significant effect on Employee Performance through Job Satisfaction P-value of 0.007 <0.05. Work From Home has a positive and insignificant effect on Employee Performance through the Work Environment P-value of 0.884> 0.05.